Exploring the Perspectives of AFL Teachers on Teacher Development Needs, with Reference to the Level of Professional Experience - AbdelWahhab, Fathiyya Refky (AUC Knowledge Fountain, 2026)
This thesis explores the perceptions of teachers of Arabic as a Foreign Language (AFL) regarding their training needs, with an attempt to examine whether those needs might vary according to the level of teaching experience. It also examines the views and reflections of AFL teachers about their training experiences; highlighting perceived strengths, weaknesses, and preferred training formats. The teaching competence examined in this study are based on the Cambridge Framework (n.d.) and the British Council CPD (1) Framework (2016). The key areas surveyed are Learning and the Learner, Teaching and Assessment, Arabic Language in the Classroom, Arabic Language Knowledge and Ability, Professional Development and Professional Values, Integrating Technology. Each of these areas comprises a range of sub-competences. Data were collected online from 76 AFL teachers through a questionnaire which was provided in Arabic and English versions and which had quantitative and descriptive sections. Of the total respondents, 57 completed the Arabic version, while 19 completed the English version. Additionally, semi-structured interviews were conducted with volunteer participants to discuss their responses more deeply. Results revealed that across the main domains explored by the questionnaire, training for teaching and assessment was the highest on demand, where training for Arabic knowledge and Ability ranked the lowest. The level of professional experience did not appear to have a significant impact on the choices of respondents, with the exception of Arabic Knowledge and Ability, where early-career teachers reported a significantly higher perceived need for training compared to senior teachers. Perceived weaknesses of teacher development programs included the over-use of theoretical, nonpractical, traditional, and sometimes outdated content, insufficient attention to trainees' individual needs and learning preferences, and a limited focus on fostering teachers’ own knowledge of the Arabic language. Regarding the strengths, participants expressed appreciation for teacher development programs that focus on teaching methods and strategies, offer opportunities for teaching practice, integrate technology and AI, incorporate trainee feedback, and encourage trainees to share their expertise with each other. (1) Continuous Professional Development